In vivo active organometallic-containing antimycotic agents. Issue 4 (15th July 2021) - Rubbiani, Riccardo; Weil, Tobias; Tocci, Noemi; Mastrobuoni, Luciano; Jeger, Severin; Moretto, Marco; Ng, James; Lin, Yan; Hess, Jeannine; Ferrari, Stefano; Kaech, Andres; Young, Luke; et al.
Abstract : Fungal infections represent a global problem and there is an urgent need for new drugs. In this work, we prepared four novel organometallic derivatives of the frontline antifungal drug fluconazole with very promising in vivo activity. Abstract : Fungal infections represent a global problem, notably for immunocompromised patients in hospital, COVID-19 patient wards and care home settings, and the ever-increasing emergence of multidrug resistant fungal strains is a sword of Damocles hanging over many healthcare systems. Azoles represent the mainstay of antifungal drugs, and their mode of action involves the binding mode of these molecules to the fungal lanosterol 14α-demethylase target enzyme. In this study, we have prepared and characterized four novel organometallic derivatives of the frontline antifungal drug fluconazole (1a–4a ). Very importantly, enzyme inhibition and chemogenomic profiling demonstrated that lanosterol 14α-demethylase, as for fluconazole, was the main target of the most active compound of the series, ( N -(ferrocenylmethyl)-2-(2, 4-difluorophenyl)-2-hydroxy- N -methyl-3-(1 H -1, 2, 4-triazol-1-yl)propan-1-aminium chloride, 2a ). Transmission electron microscopy (TEM) studies suggested that 2a induced a loss in cell wall integrity as well as intracellular features ascribable to late apoptosis or necrosis. The impressive activity of 2a was further confirmed on clinical isolates, where antimycotic potency up to 400 times higher than fluconazole was observed. Also, 2a showed activity towards azole-resistant strains. This finding is very interesting since the primary target of 2a is the same as that of fluconazole, emphasizing the role played by the organometallic moiety. In vivo experiments in a mice model of Candida infections revealed that 2a reduced the fungal growth and dissemination but also ameliorated immunopathology, a finding suggesting that 2a is active in vivo with added activity on the host innate immune response.